Potential of Botanical Lures as Attractant for Monitoring Grasshoppers (Orthoptera) on Yam (Dioscorea Rotundata)Plant in Makurdi, Benue State, Nigeria (Global Journal of Science Frontier Research, 2014)
Abstract not found
Keywords: botanical lures; attractants; grasshoppers; yam (dioscorea rotundata); monitoring; control